2020
DOI: 10.1186/s13690-020-0391-8
|View full text |Cite
|
Sign up to set email alerts
|

Working towards a better understanding of type 2 diabetes care organization with First Nations communities: a qualitative assessment

Abstract: Background: Diabetes care is suboptimal in First Nations populations. Innovative and culturally-relevant approaches are needed to promote proactive organization of diabetes care for diabetes patients on-reserve in Canada. The Reorganizing the Approach to Diabetes care through the Application of Registries (RADAR) model is one strategy to improve care: an integrated disease registry and electronic health record for community healthcare workers with centralized care coordination. The aim of this study was to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(37 reference statements)
3
5
0
Order By: Relevance
“…Where the clinics were found, they lacked the necessary material and human resources to adequately cater for people with diabetes. The finding aligns with the work of Wozniak et al ( 2020 ) who found limited financial and human resources as a hallmark issue such that healthcare workers could not undertake even screening at the health centres to identify people with T2D and therefore had to rely on the referral system. In addition, concerns have been raised about the capacity of community health workers to effectively handle people with diabetes due to the nature of their training; meanwhile, they remain instrumental in the prevention of T2D (Gore et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Where the clinics were found, they lacked the necessary material and human resources to adequately cater for people with diabetes. The finding aligns with the work of Wozniak et al ( 2020 ) who found limited financial and human resources as a hallmark issue such that healthcare workers could not undertake even screening at the health centres to identify people with T2D and therefore had to rely on the referral system. In addition, concerns have been raised about the capacity of community health workers to effectively handle people with diabetes due to the nature of their training; meanwhile, they remain instrumental in the prevention of T2D (Gore et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Where the clinics were found, they lacked the necessary material and human resources to adequately cater for people with diabetes. The finding aligns with the work of Wozniak et al (2020) who found limited financial and human resources as a hallmark issue such that healthcare workers could not undertake even screening at the health centres to identify people with T2D and therefore had to rely on the referral system. In…”
Section: Community-level Barrierssupporting
confidence: 80%
“…Tools, like Mapping the System, can be used to help understand participants' values as well as potential losses and benefits as a result of implementing a new model, process, or intervention [35]. In the case of RADAR, targeted messaging for community leaders and health centre staff, might include reframing diabetes care from reactive and episodic to proactive and preventative [8]. Messaging could capitalize on health directors' and local HCPs' focus on traditional public health, such as immunizations, to prevent disease and reframe diabetes care similarly as prevention of chronic disease [37].…”
Section: Discussionmentioning
confidence: 99%
“…These issues are compounded by suboptimal diabetes care, particularly in rural or remote settings where many First Nations people live [2,[4][5][6]. In Canada, diabetes care in First Nations communities is delivered through federally-funded nurse-led homecare, community health, and diabetes programs with limited access to primary care physicians and specialists [7] Additionally, healthcare providers in some First Nations communities in Alberta feel limited in their ability to identify, track, and manage patients with type 2 diabetes; therefore, care was typically reactive and dependent on patients' abilities to navigate the health system [8]. Clearly, there is a need for innovative and culturallyrelevant approaches to promote systematic and proactive organization of diabetes care for First Nations people living with diabetes on-reserve in Canada [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…(33) In the case of RADAR, targeted messaging for community leaders and health centre staff, might include reframing diabetes care from reactive and episodic to proactive and preventative. (8) Messaging could capitalize on health directors' and local HCPs' focus on traditional public health, such as immunizations, to prevent disease and reframe diabetes care similarly as prevention of chronic disease. (35) To increase its potential to achieve outcomes, the spread (i.e.…”
Section: Discussionmentioning
confidence: 99%